Entrepreneurs’ characteristics from the islamic perspective: A study of muslimpreneurs’ performance - Ismail A.; Ismail F.L.M.; Wahab N.A.; Latiff L.A.; Kandil H.M.T.E. (Hampstead Psychological Associates, 2024)
Indexed by Scopus/ERA